TMIC-31. IMPACT OF IRON ON MACROPHAGE IMMUNE PHENOTYPE IN THE GLIOBLASTOMA TUMOR MICROENVIRONMENT. (11th November 2019) - Shenoy, Ganesh; Madhankumar, Achuthamangalam; Slagle-Webb, Becky; Mrowczynski, Oliver; Schell, Todd; Nesterova, Darya; Lee, Sang; Davalos, Dimitrios; Berens, Michael; Lathia, Justin; Barnholtz-Sloan, Jill; Rubin, Joshua; et al.
Abstract: The tumor microenvironment (TME) in glioblastoma presents a significant hurdle to effective immunotherapies as it consists of an immunosuppressive niche that results in inhibition of anti-tumor immunity. Macrophages comprise a large portion of the glioblastoma TME as they are prolific secretors of immunosuppressive cytokines and can comprise of up to 30% of tumor volume. In addition to their crucial role in immune function, macrophages are important players in iron regulation owing to their ability to efficiently sequester and release iron. We studied the impact of iron status in macrophage anti-tumor immune functions and phenotypic plasticity using RAW264.7 macrophages and bone-marrow-derived macrophages (BMDMs). Using RAW264.7 cells, we found that the iron status of macrophages impacts their immune function by modulating expression of the co-stimulation membrane proteins CD80 and CD86 as well as the mannose receptor CD206. Interestingly, the iron-mediated immunomodulation was dependent on the formulation of iron with nanoparticle formulations such as ferumoxytol (Fe-NP) upregulating CD80, CD86, and decreasing CD206 while ferric ammonium citrate (FAC) downregulated CD80, CD86 and upregulated CD206. We analyzed expression of inflammatory cytokines in BMDMs with multiplex cytokine analysis and found that both FAC and Fe-NP increased expression of the chemotactic signals CXCL10, CCL1, CCL3, and CCL4. Additionally, we found that iron status impacts the ability of macrophages to repolarize from an inflammatory, immune-activating phenotype into an immunosuppressive phenotype upon exposure to glioblastoma tumor-conditioned media. We used qRT-PCR to examine gene expression of the tumor immunity-related genes TNFa, IL1B, NOS2, and IL10 and found that iron loaded RAW264.7 macrophages stimulated with lipopolysaccharide resisted repolarization into an immunosuppressive phenotype 24 hours after exposure to glioblastoma tumor-conditioned media. Our results suggest that understanding the link between iron status and immune function in the tumor microenvironment may be an important step in improving therapies against glioblastoma.